(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Lead Acid Batteries are traditionally used in low powered electric scooters, cars etc. from centuries. The advancement and reliability of gasoline powered vehicles surpassed Lead Acid Battery technology but advancement in electronics and battery technology revived the electric powered vehicles in recent decades. The pollution concern and price of gasoline emerged as a big problem lately. So, the e-scooters again becoming popular choice. The cheaper option of electric two-wheeler is Lead acid battery powered scooters. The model name of scooter which was checked was LY1200DQT-16F. The machine used to check performance parameters namely power, torque, RPM and speed was Two Wheelers Chassis Dynamometer. The chassis dynamometer is a machine which is used to measure the power, torque, acceleration etc. of a vehicle. The electric scooter has been fully (100%) charged and then checked the performance parameters namely the motor power, wheel power, wheel torque, RPM and speed in every 5% decrease in remaining charge percentage. The Motor Power, wheel power, maximum torque, maximum RPM and maximum speed have been decreased up to 71%, 79%, 48%, 45% and 46% respectively till lowest charge condition i.e., at 5%.